Inspecting the performance of neutral players in different small-sided games - Clemente, Filipe Manuel (2015)
The aim of this study was to inspect the effects of format and task conditions on neutral players’ heart rate responses and time-motion characteristics. Four formats of play using neutral players and three task conditions were inspected. Moreover, the factor repetition (3 games per each SSG) was also analysed. Ten male amateur soccer players (26.36 ± 5.33 years old, 8 ± 3.2 years of practice, 66.18 ± 10.16 bpm at rest) participated in this study. The repeated measured revealed that no differences were found between repetitions (Pillai’s Trace = .075; F8, 100 = 1.007; p-value = .436; = .075; Power = .445; small effect size). In the game 1 significant interaction effects between the two factors on heart rate responses and time-motion profiles were observed (Pillai’s Trace = 0.699; F24,428 = 3.774; p-value = .001; = .175; Power = 1.000; moderate effect size). In the game 2 , significant interaction effects between the two factors on heart rate responses and time-motion profiles were observed (Pillai’s Trace = .712; F24,428 = 3.860; p-value = .001; = .178; Power = 1.000; moderate effect size). Finally, in the game 3 significant interaction effects between the two factors on heart rate responses and time-motion profiles were observed (Pillai’s Trace = .729; F24,428 = 3.972; p-value = .001; = .182; Power = 1.000; moderate effect size). Briefly, it was possible to conclude that the biggest formats statistically increased the heart rate responses and time-motion characteristics of neutral players. It was also possible to observe that the mean values of heart rate responses found in neutral players throughout small-sided games were appropriated to very light or recovery workouts.